2021
DOI: 10.1002/jmv.27217
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of APEX1 p.Asp148Glu and XRCC1 p.Gln399Arg with the susceptibility of hepatocellular carcinoma

Abstract: The DNA repair genes have a crucial function in the base excision repair (BER) mechanism among different cancerous disorders, particularly hepatocellular carcinoma (HCC). The foremost objective of this study is to explore the association of genetic variants of the APEX1 p.Asp148Glu and the XRCC1 p.Gln399Arg with the susceptibility of HCC and to identify the computational bioinformatics frameworks of these missense variants. A total of 250 participants were enrolled in this study, including 150 HCC patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In our results, there was no relationship with fatty livers. Although the studied SNP has not been related to fatty livers so far, there are papers in which this polymorphism is important in diseases closely associated with fatty liver, such as diabetes [50][51][52] and HCC [12,30,53,54]. However, in our research, we did not find any correlation with NAFLD.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In our results, there was no relationship with fatty livers. Although the studied SNP has not been related to fatty livers so far, there are papers in which this polymorphism is important in diseases closely associated with fatty liver, such as diabetes [50][51][52] and HCC [12,30,53,54]. However, in our research, we did not find any correlation with NAFLD.…”
Section: Discussioncontrasting
confidence: 84%
“…Moreover, other articles demonstrated that rs1760944 increases the risk of lung and breast cancer, as well as neural tube defects, and decreases the risk of prostate cancer [26][27][28][29]. On the other hand, rs1130409 elevates the risk of HIV-1 infection, prostate cancer, and HCC and reduces cervical cancer [28,[30][31][32]. Increased expression of APEX1 has been observed in HCC patients when compared to healthy individuals [33].…”
Section: Discussionmentioning
confidence: 99%
“…HCC is a highly heterogeneous malignant tumor and often results in unstable therapeutic efficacy and inaccurate prognosis [ 18 ]. Generally, the progression of HCC is closely associated with genetic and epigenetic changes which may induce poor prognosis of HCC [ 19 , 20 ]. Particularly, considering the importance of poor prognosis of HCC, identification of accurate and specific biomarkers for HCC is required.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the second-highest cause of cancer-related mortality diagnosed worldwide [ 1 ]. It is the most challenging carcinoma to treat, and rates continue to grow rapidly: Global incidence is projected to reach over one million cases by 2025 [ 2 , 3 ]. The prevalence of HCC in Africa is highest among Egyptian individuals, which may be due to various genetic factors or to Egypt’s high hepatitis C virus (HCV) burden [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%